Desain Implementasi Rangkaian Kontrol Motor Penggerak Pisau untuk Peningkatan Produksi Onthok Yuyu - Saukani, Imam; Herwandi; Susilo, Sugeng Hadi; Sumarno, Agus Sukoco Heru; Sidik Nurcahyo; Doddy Maulana (Politeknik Negeri Malang, 2024)
Onthok yuyu is a traditional cake included in the dry cake category and is made from sticky rice flour. Onthok yuyu is also known as Onthok worm, this is because the shape of the cake resembles a mound dug up by worms or yuyu (Javanese: crab). The traditional Onthok yuyu cake outside Java is more often known as coconut root cake, because its shape resembles the roots of a coconut tree piled up on the ground. The forming process is carried out before the dry cake processing process, usually the raw material is flour mixed with liquid (water, butter) etc. to become a dough. Forming is done on the dough, then processing is carried out by frying or baking. The process of forming or molding food products on an industrial scale can be done using extrusion or molding processes. If an elongated product is desired, the forming process is extrusion, namely using an extruder machine by installing output holes whose shape and size are adjusted to the cross-section of the desired food product. If a certain shape is desired, the dough is extruded and then continued with forming or molding. Basically, molding can be done carried out by two methods. Efforts to empower Micro, Small and Medium Enterprises (MSMEs) require an empowerment model that includes improving existing MSMEs so that they are more advanced so they can strictly competent in free market competition.